Highly Efficient Generation of Transgenically Augmented CAR NK Cells Overexpressing CXCR4 - Jamali, Arezoo; Hadjati, Jamshid; Madjd, Zahra; Mirzaei, Hamid Reza; Thalheimer, Frederic B.; Agarwal, Shiwani; Bonig, Halvard; Ullrich, Evelyn; Hartmann, Jessica (Frontiers in Immunology, 2020)
Natural killer (NK) cells are a noteworthy lymphocyte subset in cancer adoptive cell therapy. NK cells initiate innate immune responses against infections and malignancies with natural cytotoxicity which is independent of foreign antigen recognition. Based on these substantive features, genetically modifying NK cells is among the prime goals in immunotherapy but is currently difficult to achieve. Recently we reported a fully human CAR19 construct (huCAR19) with remarkable function in gene-modified T cells. Here we show efficient and stable gene delivery of huCAR19 to primary human NK cells using lentiviral vectors with transduction efficiencies comparable to those achieved with NK cell lines. These huCAR19 NK cells displayed specific and potent cytotoxic activity against target cells. To improve homing of NK cells to the bone marrow, we augmented huCAR19 NK cells with the human CXCR4 gene, resulting in transgenically augmented CAR NK cells (TRACKs). Compared to conventional CAR NK cells, TRACKs exhibited enhanced migration capacity in response to recombinant SDF-1 or bone marrow stromal cells, while retaining functional and cytolytic activity against target cells. Based on these promising findings, TRACKs may become a novel candidate for immunotherapeutic strategies in clinical applications.